Social Networks, Political Power and Family. An Analysis based on the Posse Talavera family of Tucumán (1830-1870) - Bolsi, Francisco (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article analyzes the social networks and political power of the Tucumán elite, based on a study of the Posse Talavera family from 1830 to 1870. Data collection sources included the Finance and Administrative Section, Civil Judicial Section, and Protocole Section of the Tucumán Historic Archive. This information was complemented by bibliographic production on the studied period. The study is based on the hypothesis that the Posse Talavera family constituted a social and power network, by means of formal ties -matrimonial alliances- and informal ones -relations of loyalty and reciprocity-; this network situated the family in the scene of provincial politics in the decade of 1860 and allowed for the accumulation of signiicant assets by means of their economic activities. These ties transcended the local and regional sphere in consonance with the construction of the Modern Argentinian State.